Efficiency and Redistribution: An Evaluative Review of Louis Kaplow's The Theory of Taxation and Public Economics - Boadway, Robin (Journal of Economic Literature, 2010)
Louis Kaplow proposes a two-step methodology for normative policy analysis and illustrates it using various policy reforms. The first step is to identify efficiency gains when hypothetical lump-sum taxes can undo redistributive consequences. The second step evaluates the redistributive effects using a strictly welfaristic social welfare function. I critically review the foundations for Kaplow's procedure and its reliance on strict welfarism. I argue that basing efficiency gains on hypothetical lump-sum tax adjustments can lead to social welfare reducing policies if such tax adjustments are not carried out. I also indicate some conceptual problems with translating welfarism into policy evaluation when individuals have different utility function, and review one promising alternative approach.(JEL H20, H41, H50)